A Study of the Effect of Religiousity on Attitude into Water Saving in Yasouj - Siroos Ahmadi; ghasem zareei (توسعه اجتماعی)
Water is a vital resourc that potentially affects on all aspects of everyday life but optimal use of water has not yet formed Iran. The main goal of this research is to investigate effect of religiousity on attitude toward home water-saving. The survey method was used in this study. The population was all of citizens over the age of 18 in Yasouj that 400 cases were selected using multi-stage random sampling method. Research instrument for collecting data, was a researcher-made questionnaire that construct validity through factor analysis technique, was used for determination of the validity and the reliability was measured by cronbach Alpha coefficient. Research findings using structural equation model showed that religiousity has a significant and positive effect on the attitude toward home water-saving and can significantly predict variance of home water-saving. Research findings also showed that there is no significant relationship between demographic variables and home water is saving.